PENERAPAN MODEL PKR 222 TERHADAP EFEKTIVITAS BELAJAR SISWA KELAS 5 DAN 6 DI SDN4 MASBAGIK UTARA - Rita Suria Perdana; Siti Nurul Fitriani; Siti Zainab Muslimin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research describes the implementation of Multi-Grade Classroom Model 222 (PKR 222) and its impact on learning effectiveness for fifth and sixth-grade students at SDN 4 Masbagik Utara, Lombok Timur. The problem arises from limited classroom space over six years, compelling teachers to combine grades 5 and 6, resulting in unbalanced interactions, student distractions, and suboptimal outcomes. PKR 222 addresses this using two grades, two subjects, and two adjacent rooms connected by one door. A descriptive qualitative approach was employed, collecting data via participatory observation in three sessions (2 × 35 minutes each) and documentation (lesson plans, worksheets, reflections, photos, videos) from one teacher and 52 students (24 in grade 5, 28 in grade 6). Analysis followed Miles and Huberman’s model: reduction, display, and conclusion, validated by source/method triangulation and member checks. Results show progressive gains: teacher activity from 80% (good) to 95% (very high), student activity from 65% (fair) to 95% (very high), and learning effectiveness from 65% (moderate) to 95% (very high). The model fosters independence, active participation, peer tutoring, and responsibility, while enabling efficient teacher management and resource use per PKR principles. Thus, PKR 222 proves an effective strategy for resource-limited primary schools.